Method for improving the comprehensive performance coefficient of magnesium alloys
Patent Information
- Application Number
- CN202510612698.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-13
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-05-13
AI Technical Summary
Existing magnesium alloys have insufficient thermal conductivity and elongation after the addition of alloying elements, and their overall performance coefficient needs to be improved. Furthermore, excessive addition of rare earth elements leads to problems such as high production costs or excessively low elongation.
Magnesium alloys were prepared by controlling the content of La and Mn in magnesium alloys and using SF6 and N2 as protective gases, and by melting, stirring, refining, casting and extruding under specific temperature and conditions, thereby optimizing the balance between thermal conductivity and elongation.
The overall performance coefficient of magnesium alloys was significantly improved, with both thermal conductivity and elongation increased, resulting in a significant improvement in overall performance.
Abstract
Description
Technical Field
[0001] This invention relates to a method for improving the overall performance coefficient of magnesium alloys. Background Technology
[0002] Currently, the main heat dissipation alloy materials are copper alloys, aluminum alloys, and magnesium alloys. Among them, pure copper has the highest thermal conductivity at 397 W / (m·K), pure aluminum at 247 W / (m·K), and pure magnesium at 158 W / (m·K). Although magnesium's thermal conductivity is lower than that of copper and aluminum, it has the characteristics of low density, high specific strength and specific stiffness, good vibration damping, and good electromagnetic shielding performance. As a material for electronic device housings, it can well meet the requirements of lightweight and small size. Therefore, magnesium has unique advantages as a heat sink material for electronic devices.
[0003] According to the theory of thermal conductivity, adding alloying elements to the matrix, whether forming a solid solution or a second phase, will significantly reduce the thermal conductivity of the material. The reason why adding alloying elements reduces the thermal conductivity of magnesium alloys is that there is a difference in atomic radius between the alloying elements and magnesium. The addition of alloying elements causes a periodic change in the magnesium matrix lattice, resulting in lattice distortion. This affects the free movement of electrons within the lattice, reduces the mean free path of electrons, and thus lowers the thermal conductivity of the magnesium alloy material. Therefore, those skilled in the art have been continuously improving magnesium alloys to address the above problems.
[0004] CN113322404A discloses a high thermal conductivity and high strength Mg-Al-La-Mn wrought magnesium alloy, comprising Al: 2.8–3.5 wt%, La: 4.3–5.0 wt%, Mn: 0.28–0.3 wt%, with Mg as the balance. The method reduces the influence of La on the thermal conductivity of the magnesium alloy by forming a second phase with highly dissolved Al, resulting in a magnesium-aluminum alloy system. However, the formed second phase affects the alloy's thermal conductivity and cannot completely eliminate the adverse effects of Al addition on thermal conductivity. Its overall performance still needs improvement.
[0005] CN116732401A discloses a high-strength, high-thermal-conductivity deformable magnesium alloy Mg-xZn-0.5Mn-yRE with added mixed rare earth elements, wherein x is 0.5–3 wt%, y < 0.5 wt%, and RE is composed of any La and Ce mixing ratio, and RE is added through a Mg-30La / Ce mixed rare earth master alloy (the La / Ce mass ratio in the master alloy is arbitrary). The rare earth elements added to this magnesium alloy are a combination of La and Ce. Adding too many types of elements to the alloy can negatively impact its thermal conductivity and lead to excessively high production costs. More importantly, the solid solubility of Zn in the magnesium matrix (2.40 at%) is much greater than that of La (0.14 at%), weakening the strengthening effect of La.
[0006] CN117026036A discloses a high thermal conductivity, high strength wrought magnesium alloy Mg-Mn-X; wherein X is a light rare earth element with a content of 0.5–5.0 wt%, and Mn has a content of 0.5–4.0 wt%; the balance is Mg and unavoidable impurities. The high content of rare earth elements in this magnesium alloy results in excessively low elongation.
[0007] CN118773497A discloses a high thermal conductivity and high strength wrought magnesium alloy containing high abundance of rare earth elements, composed of 1.45–1.55 wt% Zn, 0.45–0.55 wt% Mn, 0.15–1.5 wt% La, and the balance Mg and unavoidable impurities. The solid solubility of Zn in the magnesium matrix (2.40 at%) is much greater than that of La (0.14 at%), which weakens the strengthening effect of La. Summary of the Invention
[0008] In view of this, one object of the present invention is to provide a method for improving the overall performance coefficient of magnesium alloys, which can significantly improve the thermal conductivity and elongation of magnesium alloys, resulting in a higher overall performance coefficient.
[0009] The present invention achieves the above objectives using the following technical solutions.
[0010] This invention provides a method for improving the overall performance coefficient of magnesium alloys, comprising the following steps:
[0011] 1) Provide raw materials according to the chemical composition of the magnesium alloy and preheat the raw materials; wherein, the chemical composition of the magnesium alloy is as follows by weight percentage: La 0.8~1.2wt%, Mn 0.2~1.0wt%, the balance being magnesium and unavoidable impurities; the raw materials include magnesium ingots, magnesium-lanthanum master alloy and manganese powder;
[0012] 2) Melt the preheated magnesium ingot under a protective gas and at 680-750°C to obtain molten magnesium; wherein the protective gas is composed of SF6 and N2, and the volume ratio of SF6 to N2 is 1:300-800.
[0013] 3) Under protective gas and at 700-800°C, the preheated magnesium-lanthanum master alloy is added to the magnesium melt to melt the magnesium-lanthanum master alloy. Then, the preheated manganese powder is added and stirred for 60-150 minutes to obtain a mixture. The mixture is then refined and slag-removed to obtain a magnesium alloy liquid. The protective gas consists of SF6 and N2, with a volume ratio of SF6 to N2 of 1:300-800.
[0014] 4) Pour the molten magnesium alloy into a mold at 650-750°C and cool to obtain a primary magnesium alloy ingot;
[0015] 5) Anneal the primary magnesium alloy ingot, and then extrude it at 200-500℃ to obtain a magnesium alloy;
[0016] Wherein, the comprehensive performance coefficient ε=λ×δ; where λ is the thermal conductivity, in W / (m·K); and δ is the elongation, in %.
[0017] According to the method of the present invention, preferably, in step 1), the chemical composition of the magnesium alloy is as follows by weight percentage: La 0.85-1.15wt%, Mn 0.3-0.8wt%, with the balance being magnesium and unavoidable impurities.
[0018] According to the method of the present invention, preferably, in step 1), the preheating temperature is 100-300°C and the preheating time is 1-8 hours.
[0019] According to the method of the present invention, preferably, in step 2), the volume ratio of SF6 to N2 is 1:350 to 650.
[0020] According to the method of the present invention, preferably, in step 3), the volume ratio of SF6 to N2 is 1:350 to 650.
[0021] According to the method of the present invention, preferably, in step 3), argon gas is used to refine the mixture, and the flow rate of argon gas is 80-150 cm³. 3 / min.
[0022] According to the method of the present invention, preferably, in step 3), after slag removal, the mixture is allowed to stand for 45-90 minutes, and then allowed to stand for another 20-60 minutes at 680-780°C to obtain magnesium alloy liquid.
[0023] According to the method of the present invention, preferably, in step 5), the extrusion is forward extrusion and the extrusion ratio is 12 to 20:1.
[0024] According to the method of the present invention, preferably, the comprehensive performance coefficient ε of the magnesium alloy is 15 W / (m·K) or higher.
[0025] According to the method of the present invention, preferably, the elongation δ of the magnesium alloy is 12% or more, and the thermal conductivity λ is 124 W / (m·K) or more;
[0026] The elongation δ was measured in accordance with GB / T228.1-2021; the thermal conductivity λ was measured using a NETZSCH LFA427 laser thermal conductivity meter.
[0027] This invention improves the overall performance coefficient of magnesium alloys by controlling the content of La and Mn in the magnesium alloys and using SF6 and N2 as protective gases. Detailed Implementation
[0028] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0029] The "elongation" mentioned in this invention refers to the percentage of the elongation of the gauge length segment after the object breaks during the stretching process, compared to the original gauge length, and is usually expressed as "%".
[0030] The "thermal conductivity" mentioned in this invention refers to the thermal conductivity of two parallel planes, each 1 meter apart and with an area of 1 square meter, taken perpendicular to the direction of heat conduction inside an object. If the temperature difference between the two planes is 1 K, then the amount of heat conducted from one plane to the other in 1 second is the thermal conductivity, with the unit being W / (m·K).
[0031] Methods to Improve the Overall Performance Coefficient of Magnesium Alloys
[0032] This invention provides a method for improving the overall performance coefficient of magnesium alloys. The overall performance coefficient ε is characterized by the following formula:
[0033] ε=λ×δ
[0034] The overall performance coefficient ε = λ × δ; where λ is the thermal conductivity, in W / (m·K); and δ is the elongation, in %.
[0035] Thermal conductivity represents the thermal conductivity of magnesium alloys, while elongation represents their plasticity. These two parameters are the most important indicators of magnesium alloys, and their product represents the overall performance of the alloy. The larger the overall performance coefficient ε, the better the overall performance of the magnesium alloy.
[0036] The method of the present invention includes the following steps: raw material preparation, magnesium ingot melting, magnesium alloy liquid preparation, primary magnesium alloy ingot preparation, and extrusion. These are described in detail below.
[0037] Raw material preparation steps
[0038] Raw materials are provided according to the chemical composition of the magnesium alloy, and the raw materials are preheated.
[0039] According to one embodiment of the present invention, the chemical composition of the magnesium alloy is as follows by weight percentage: La 0.8-1.2 wt%, Mn 0.2-1.0 wt%, with the balance being magnesium and unavoidable impurities.
[0040] In the magnesium alloy of the present invention, the amount of La, by weight percentage, can be 0.8–1.2 wt%, preferably 0.85–1.15 wt%, and more preferably 0.9–1.1 wt%. In the magnesium alloy of the present invention, the amount of Mn, by weight percentage, can be 0.2–1.0 wt%, preferably 0.3–0.8 wt%, and more preferably 0.4–0.6 wt%. Controlling the amounts of La and Mn within the above ranges is beneficial for balancing the thermal conductivity and mechanical properties of the magnesium alloy, thereby ensuring that the magnesium alloy possesses both good thermal conductivity and elongation, thus improving the overall performance of the magnesium alloy. Exceeding the above ranges in the amounts of La and Mn will adversely affect the overall performance of the magnesium alloy.
[0041] According to one specific embodiment of the present invention, the chemical composition of the magnesium alloy is as follows by weight percentage: La 0.85-1.15wt%, Mn 0.3-0.8wt%, with the balance being magnesium and unavoidable impurities.
[0042] According to a preferred embodiment of the present invention, the chemical composition of the magnesium alloy is as follows by weight percentage: La 0.9-1.1 wt%, Mn 0.4-0.6 wt%, with the balance being magnesium and unavoidable impurities.
[0043] The raw materials of this invention may include magnesium ingots, magnesium-lanthanum master alloy, and manganese powder. Preferably, the raw materials of this invention consist of magnesium ingots, magnesium-lanthanum master alloy, and manganese powder. The magnesium ingots, magnesium-lanthanum master alloy, and manganese powder used in this invention can be commercially available products or prepared by existing methods. The purity of the raw materials of this invention is at least 99.98 wt%.
[0044] In the magnesium-lanthanum master alloy, the mass percentage of lanthanum can be 5 to 50 wt%, preferably 10 to 50 wt%, and more preferably 10 to 30 wt%.
[0045] According to one embodiment of the present invention, the preheating temperature can be 100–300°C, preferably 120–280°C, and more preferably 150–250°C. The preheating time can be 1–8 hours, preferably 2–7 hours, and more preferably 3–6 hours. Reasonable preheating conditions are beneficial for removing moisture and impurities, reducing hydrogen embrittlement and hot cracking tendencies, and preventing the raw materials from being oxidized, thereby ensuring that the magnesium alloy has good comprehensive properties.
[0046] Steps for melting magnesium ingots
[0047] Magnesium ingots are melted under a protective gas and at 680–750°C to obtain molten magnesium.
[0048] According to one embodiment of the present invention, the protective gas is a mixture of SF6 (sulfur hexafluoride) and N2 (nitrogen), wherein the volume ratio of SF6 to N2 can be 1:300 to 800, preferably 1:350 to 650, and more preferably 1:400 to 600. Such melting conditions facilitate the complete melting of magnesium ingots to form molten magnesium, prevent particle residue in the molten magnesium, and thereby improve the overall performance of the magnesium alloy. The present invention has found that replacing carbon dioxide with nitrogen can significantly improve the overall performance coefficient of magnesium alloys, although the principle is not yet clear.
[0049] According to one embodiment of the present invention, the melting temperature can be 680-750°C, preferably 685-745°C, and more preferably 690-740°C.
[0050] Magnesium alloy liquid preparation steps
[0051] Under protective gas and at 700–800°C, the preheated magnesium-lanthanum master alloy is added to the magnesium melt to melt the magnesium-lanthanum master alloy. Then, the preheated manganese powder is added and stirred for 60–150 minutes to obtain a mixture. The mixture is then refined and slag-removed to obtain a magnesium alloy liquid.
[0052] According to one embodiment of the present invention, the protective gas is a mixture of SF6 (sulfur hexafluoride) and N2 (nitrogen), wherein the volume ratio of SF6 to N2 can be 1:300 to 800, preferably 1:350 to 650, and more preferably 1:400 to 600. The present invention has found that replacing carbon dioxide with nitrogen can significantly improve the overall performance coefficient of magnesium alloys, although the principle is not yet clear.
[0053] According to one embodiment of the present invention, the temperature at which the magnesium-lanthanum master alloy is added can be 700-800°C, preferably 710-790°C, and more preferably 720-780°C.
[0054] According to one embodiment of the present invention, the stirring time can be 60-150 min, preferably 70-130 min, and more preferably 80-120 min.
[0055] In this invention, stirring can be achieved using any method or device known in the art, which will not be elaborated here.
[0056] According to one embodiment of the present invention, argon (Ar) is used to refine the mixture, and the flow rate of argon can be 80-150 cm³. 3 / min, preferably 85-135cm 3 / min, more preferably 90-120cm 3 / min.
[0057] According to one embodiment of the present invention, slag removal may include the following steps:
[0058] a) Dry the slag remover at 200-500℃ for 2-6 hours, and then add the dried slag remover to the refined mixture at 700-800℃ to melt the slag remover;
[0059] b) Next, stir the mixture at 60-120 rpm for 10-20 minutes, then let the mixture stand for 20-60 minutes. Then remove the slag on the surface and the mixture with a thickness of 5-10 mm below the slag to obtain the slag-removed mixture.
[0060] According to a specific embodiment of the present invention, in step a), the drying temperature can be 200–500°C, preferably 200–400°C, and more preferably 250–400°C. The drying time can be 2–6 hours, preferably 2–5 hours, and more preferably 3–5 hours.
[0061] According to a specific embodiment of the present invention, in step a), the temperature at which the dried slagging agent is added can be 700-800°C, preferably 750-800°C, and more preferably 750-790°C.
[0062] According to a specific embodiment of the present invention, in step b), the stirring speed can be 60-120 rpm, preferably 65-115 rpm, more preferably 70-110 rpm. The stirring time can be 10-20 min, preferably 12-20 min, more preferably 12-18 min.
[0063] According to a specific embodiment of the present invention, in step b), the time for the mixture to stand can be 20 to 60 minutes, preferably 20 to 50 minutes, and more preferably 25 to 50 minutes.
[0064] According to a specific embodiment of the present invention, in step b), the thickness of the mixture below the slag removal liquid can be 5 to 10 mm, preferably 6 to 10 mm, and more preferably 6 to 9 mm.
[0065] In this invention, the slag remover can be a commercially available product or can be formulated with reference to existing slag remover formulas, which will not be elaborated here.
[0066] According to a preferred embodiment of the present invention, the slagging agent is made of the following components by weight percentage:
[0067] MgCl2 32–38 wt%, KCl 31–37 wt%, BaCl2 10–16 wt%, CaF2 6–12 wt%, CaCl2 1–7 wt%, NaCl 1–7 wt%, and MgO 0.5–2 wt%.
[0068] In the slag-removing agent raw materials of the present invention, the amount of MgCl2 can be 32-38 wt%, preferably 33-37 wt%, more preferably 34-36 wt%. The amount of KCl can be 31-37 wt%, preferably 32-36 wt%, more preferably 33-35 wt%. The amount of BaCl2 can be 10-16 wt%, preferably 11-15 wt%, more preferably 12-14 wt%. The amount of CaF2 can be 6-12 wt%, preferably 7-11 wt%, more preferably 8-10 wt%. The amount of CaCl2 can be 1-7 wt%, preferably 2-6 wt%, more preferably 3-5 wt%. The amount of NaCl can be 1-7 wt%, preferably 2-6 wt%, more preferably 3-5 wt%. The amount of MgO can be 0.5-2 wt%, preferably 0.6-1.8 wt%, more preferably 0.8-1.6 wt%.
[0069] The slagging agent can be added in any way that is possible in this field, and will not be elaborated here. For example, it can be added by rotating the fabric.
[0070] According to one embodiment of the present invention, after slag removal, the mixture can be left to stand for 45 to 90 minutes, preferably 50 to 85 minutes, and more preferably 55 to 80 minutes.
[0071] According to one embodiment of the present invention, the mixture can be allowed to stand again at 680–780°C for 20–60 minutes to obtain a magnesium alloy liquid. The temperature for further standing of the mixture can be 680–780°C, preferably 690–770°C, and more preferably 700–760°C. The time for further standing of the mixture can be 20–60 minutes, preferably 25–55 minutes, and more preferably 30–50 minutes. Using the above process conditions is beneficial for improving the overall properties of the magnesium alloy.
[0072] Primary magnesium alloy ingot preparation steps
[0073] The molten magnesium alloy is poured into a mold at 650–750°C and cooled to obtain a primary magnesium alloy ingot.
[0074] According to one embodiment of the present invention, the pouring temperature can be 650-750°C, preferably 660-740°C, and more preferably 670-720°C.
[0075] According to one embodiment of the present invention, the mold can be preheated at 100–300°C before casting. In this invention, the preheating temperature of the mold can be 100–300°C, preferably 120–280°C, and more preferably 150–250°C.
[0076] In this invention, the mold can be any magnesium alloy mold known in the art, such as a high-temperature resistant cast iron mold.
[0077] In this invention, cooling can be achieved using any method or device known in the art, including but not limited to air cooling, wind cooling, or water cooling.
[0078] Reasonable casting conditions are beneficial to improving the fluidity and microstructure uniformity of the alloy, ensuring that the magnesium alloy has both good thermal conductivity and elongation, thereby improving the overall performance coefficient of the magnesium alloy.
[0079] Extrusion steps
[0080] The primary magnesium alloy ingot is annealed and then extruded at 200–500°C to obtain a magnesium alloy.
[0081] According to one embodiment of the present invention, annealing is performed on a heat-treated magnesium alloy ingot at 300–500°C for 10–20 hours.
[0082] According to one specific embodiment of the present invention, the heat treatment temperature can be 300-500°C, preferably 320-480°C, more preferably 350-450°C. The heat treatment time can be 10-20 hours, preferably 12-18 hours, more preferably 13-17 hours.
[0083] According to a preferred embodiment of the present invention, the step of turning the surface of the annealed primary magnesium alloy ingot may also be included.
[0084] According to one specific embodiment of the present invention, the annealed primary magnesium alloy ingot can be machined into a cylinder. The outer diameter of the cylinder can be 20-60 mm, preferably 25-55 mm, and more preferably 30-50 mm. The height of the cylinder can be 20-60 mm, preferably 25-55 mm, and more preferably 30-50 mm. Appropriate machining conditions can make the surface of the primary magnesium alloy ingot smoother, which is beneficial to improving the stability of the extrusion process.
[0085] According to a preferred embodiment of the present invention, the extrusion can be forward extrusion.
[0086] According to one embodiment of the present invention, the extrusion temperature can be 200-500°C, preferably 250-450°C, and more preferably 300-400°C.
[0087] According to one embodiment of the present invention, the extrusion ratio can be 12 to 20:1, preferably 13 to 19:1, and more preferably 14 to 18:1. Using the above extrusion conditions is beneficial for refining grains and improving microstructure uniformity, thereby increasing the overall performance coefficient of the magnesium alloy.
[0088] In this invention, extrusion can be performed using any equipment known in the art, such as a forward single-action extruder or a forward double-action extruder.
[0089] According to one embodiment of the present invention, the comprehensive performance coefficient ε of the magnesium alloy is at least 15 W / (m·K), preferably at least 15.2 W / (m·K), and more preferably at least 15.4 W / (m·K).
[0090] According to one embodiment of the invention, the elongation of the magnesium alloy can be at least 12%, preferably at least 12.2%, more preferably at least 12.3%. The thermal conductivity is at least 124 W / (m·K), preferably at least 124.2 W / (m·K), more preferably at least 124.5 W / (m·K).
[0091] <Testing Method>
[0092] Elongation test: The test shall be conducted in accordance with GB / T228.1-2021.
[0093] Thermal conductivity test: The test was performed using a NETZSCH LFA427 laser thermal conductivity meter.
[0094] <Ingredient Description>
[0095] Unless otherwise specified, all raw materials used in the following examples are commercially available products.
[0096] The slagging agent is composed of the following components by weight percentage:
[0097] MgCl2 35wt%, KCl 34wt%, BaCl2 13wt%, CaF2 9wt%, CaCl2 4wt%, NaCl 4wt%, and MgO 1wt%.
[0098] Example 1
[0099] The chemical composition of the magnesium alloy, by weight percentage, is as follows: La 1.0 wt%, Mn 0.5 wt%, with the balance being magnesium and unavoidable impurities. It is prepared using the following steps:
[0100] 1) Provide magnesium ingots, Mg-25wt%La master alloy and manganese powder according to the chemical composition of the magnesium alloy, and preheat the magnesium ingots, Mg-25wt%La master alloy and manganese powder at 200℃ for 5h.
[0101] 2) Place the magnesium ingot in a resistance furnace and melt the preheated magnesium ingot under a protective gas (a mixture of SF6 and N2 with a volume ratio of 1:500) and at 720°C to obtain molten magnesium.
[0102] 3) Under a protective gas atmosphere (a mixture of SF6 and N2 at a volume ratio of 1:500) and at 740℃, the preheated Mg-25wt%La master alloy was added to the molten magnesium to melt it. Then, preheated manganese powder was added and stirred for 90 minutes to obtain a mixed solution. A flow rate of 100 cm⁻¹ was used. 3 The mixture is refined with argon gas at a flow rate of / min; then the slag remover is dried at 300℃ for 3h, and then the dried slag remover is added to the refined mixture at 780℃ using a rotating cloth method to melt the slag remover. The mixture is then stirred at 85rpm for 15min, and then allowed to stand for 30min. The slag on the surface and the 8mm thick mixture below the slag are then removed to obtain the slag-removed mixture. The slag-removed mixture is then allowed to stand for 60min, and then allowed to stand again at 720℃ for 30min to obtain the magnesium alloy liquid.
[0103] 4) Preheat the iron casting mold at 200℃, then pour the magnesium alloy liquid into the preheated iron casting mold at 680℃, and then air cool it to room temperature (25℃) to obtain the primary magnesium alloy ingot.
[0104] 5) The primary magnesium alloy ingot is heat-treated at 400℃ for 15 hours for annealing. Then, the surface of the primary magnesium alloy ingot is machined into a cylinder with an outer diameter of 40mm and a height of 40mm. The machined primary magnesium alloy ingot is then extruded at 350℃ with an extrusion ratio of 16:1 to obtain the magnesium alloy.
[0105] Comparative Example 1
[0106] Except for the following parameters and settings, everything else is the same as in Example 1:
[0107] In this comparative example, the chemical composition of the magnesium alloy, by weight percentage, is as follows: La 0.2wt%, Mn 0.5wt%, with the balance being magnesium and unavoidable impurities.
[0108] The preheating time for step 1) is 3 hours. The pouring temperature for step 4) is 700℃.
[0109] Comparative Example 2
[0110] Except for the following parameters and settings, everything else is the same as in Example 1:
[0111] In this comparative example, the chemical composition of the magnesium alloy, by weight percentage, is as follows: La 0.6wt%, Mn 0.5wt%, with the balance being magnesium and unavoidable impurities.
[0112] The preheating time for step 1) is 4 hours. The pouring temperature for step 4) is 690℃.
[0113] Comparative Example 3
[0114] Except for the following parameters and settings, everything else is the same as in Example 1:
[0115] In this comparative example, the chemical composition of the magnesium alloy, by weight percentage, is as follows: La 2.0 wt%, Mn 0.5 wt%, with the balance being magnesium and unavoidable impurities.
[0116] The preheating time for step 1) is 4 hours. The pouring temperature for step 4) is 690℃.
[0117] Comparative Example 4
[0118] The experiment was conducted according to Example 5 of CN117026036A, and the test results are shown in Table 1.
[0119] Experimental Example 1
[0120] The elongation and thermal conductivity of the magnesium alloys prepared in Example 1 and Comparative Examples 1-3 were tested. The test results are shown in Table 1.
[0121] Table 1 Performance test results of magnesium alloys
[0122] Group Elongation (%) Thermal conductivity (W / (m·K)) Overall performance coefficient (W / (m·K)) Example 1 12.39 124.64 15.44 Comparative Example 1 8.44 128.50 10.85 Comparative Example 2 9.78 125.00 12.22 Comparative Example 3 9.83 124.00 12.19 Comparative Example 4 8.1 138.70 11.23
[0123] As shown in Table 1, the magnesium alloy prepared by this invention has both higher elongation and thermal conductivity, and a higher overall performance coefficient.
[0124] This invention is not limited to the above-described embodiments. Any modifications, improvements, or substitutions that can be conceived by those skilled in the art without departing from the essential content of this invention fall within the scope of this invention.
Claims
1. A method for improving the comprehensive performance coefficient of magnesium alloys, characterized in that, Includes the following steps: 1) Provide raw materials according to the chemical composition of the magnesium alloy, and preheat the raw materials at 150-250℃ for 3-6 hours; wherein, the chemical composition of the magnesium alloy is as follows by weight percentage: La 0.9-1.1wt%, Mn 0.4-0.6wt%, with the balance being magnesium and unavoidable impurities; the raw materials include magnesium ingots, magnesium-lanthanum master alloy and manganese powder; 2) Melt the preheated magnesium ingot under a protective gas and at 690-740°C to obtain molten magnesium; wherein the protective gas is composed of SF6 and N2, and the volume ratio of SF6 to N2 is 1:500-600. 3) Under protective gas and at 720–780°C, the preheated magnesium-lanthanum master alloy is added to the molten magnesium, and the magnesium-lanthanum master alloy is melted. Then, the preheated manganese powder is added and stirred for 80–120 min to obtain a mixed solution. The mixed solution is then refined and slag-removed. The slag-removing agent is composed of the following components by weight percentage: MgCl2 32–38 wt%, KCl 31–37 wt%, BaCl2 10–16 wt%, CaF2 6–12 wt%, CaCl2 1–7 wt%, NaCl 1–7 wt%, and MgO 0.5–2 wt%. After slag removal, the mixed solution is allowed to stand for 55–80 min, and then allowed to stand again at 700–760°C for 30–50 min to obtain a magnesium alloy liquid. The protective gas consists of SF6 and N2, with a volume ratio of SF6 to N2 of 1:500–600. 4) Pour the molten magnesium alloy into a mold at 670-720℃ and cool it to obtain a primary magnesium alloy ingot; 5) Anneal the primary magnesium alloy ingot at 350–450°C for 13–17 h, and then machine the annealed primary magnesium alloy ingot into a cylinder with an outer diameter of 30–50 mm and a height of 30–50 mm. Then, extrude the cylinder at 300–400°C at an extrusion ratio of 14–18:1 to obtain a magnesium alloy. The elongation δ of the magnesium alloy is above 12.3%, the thermal conductivity λ is above 124.5 W / (m•K), and the comprehensive performance coefficient ε of the magnesium alloy is above 15.4 W / (m•K). Wherein, the comprehensive performance coefficient ε = λ × δ; where λ is the thermal conductivity, in W / (m•K); and δ is the elongation, in % (%). Elongation was measured in accordance with GB / T228.1-2021; thermal conductivity was measured using a NETZSCH LFA427 laser thermal conductivity meter.
2. The method according to claim 1, characterized in that, In step 3), argon gas is used to refine the mixture, with a flow rate of 80–150 cm³. 3 / min.
Citation Information
Patent Citations
High-thermal-conductivity and high-strength Mg-Al-La-Mn wrought magnesium alloy and preparation method thereof
CN113322404A
High-thermal-conductivity and high-strength wrought magnesium alloy and preparation method thereof
CN117026036A
